Implementation of Integrative Holistic Early Childhood Development in Realizing Child Friendly Schools in Integrated Islamic Kindergarten Bintang Kecil Bulu Lor Semarang City - Nur Intan Rochmawati (International Conference on Science, Education, and Technology, 2021)
Education from an early age is very important, for that it needs to be closely guarded. This age is very potential to get the right stimulation. Holistic stimulation services include education, health, nutrition, care, nurturing, protection and welfare services. The number of kindergartens that provide services to their students in a holistic and integrative way is still low. This is due to the limited funds owned by the institution/TK to fulfill the coverage of HI PAUD. In addition, the socialization of the National Action Plan (RAN) for HI PAUD has not yet reached the lower levels, namely the regions and the community. There are still many agencies that do not understand this, so when TK submits a request for cooperation as a partner, they still get a negative response. This gap needs to be resolved immediately so that the RAN PAUD HI can be realized throughout Indonesia. The purpose of this study was to obtain an overview of the implementation of Integrative Holistic Early Childhood Development in the Integrated Islamic Kindergarten Bintang Kecil Bulu Lor Semarang City. This study uses a qualitative approach, Creswell states qualitative research as a complex picture, examines words, reports detailed from the views of respondents and conducts studies in natural situations. This study uses a descriptive qualitative research method and uses data analysis through the stages of data collection, data presentation and conclusion drawing. Implementation of Integrative Holistic Early Childhood Development in Bintang Kecil Bulu Lor Islamic Kindergarten in Semarang City by providing education, health, nutrition, care, nurturing, protection and welfare packaged in a curriculum that has been adapted to the 2013 PAUD curriculum with a combination of 9 pillars of character education books from the Indonesia Heritage Foundation in honing religious and moral values. The conclusion in this study is that the Integrated Islamic Kindergarten of Bintang Kecil Bulu Lor Semarang City in providing HI PAUD services runs according to the technical and implementation guidelines as stated in Presidential Decree Number 60 of 2013. Semarang City Hall.